(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
У статті розглянуто значення ляльки в житті дитини. Позначені виховні, розвиваючи та освітніможливості лялькотерапії.